Barriers to Physical Activity Among Adolescent Girls During Menstruation: A Global Systematic Literature Review - Heri Mazmur; M.Elza Fahlevi Ramadhan; ⁠Dea Lendra Ginting (IGI Active Living and Health Insight, 2026)
Purpose: Menstruation constitutes a critical, yet frequently overlooked, determinant of physical activity (PA) participation among adolescent girls globally. This systematic literature review aimed to identify, synthesize, and critically evaluate the multidimensional barriers — physiological, psychological, socio-cultural, environmental, and institutional — that impede regular PA engagement among adolescent girls (aged 10–19 years) during menstruation, and to provide evidence-based insights for scholars, health practitioners, educators, and policymakers. Materials for Analysis: Following PRISMA 2020 guidelines, a systematic search was conducted across three major academic databases — Scopus, Web of Science, and PubMed — encompassing peer-reviewed studies published between January 2013 and December 2023. Boolean search strategies combining terms related to menstruation, physical activity, barriers, and adolescent girls were applied. Studies were eligible if they focused on girls aged 10–19, were published in English, and empirically addressed barriers to PA during menstruation. Following rigorous screening and quality appraisal, a total of 42 studies from 28 countries were included in the final synthesis. Results: Five overarching thematic clusters of barriers were identified: (1) physiological barriers, predominantly dysmenorrhea, fatigue, and perceived physical discomfort; (2) psychological barriers, encompassing menstrual stigma, body image concerns, and fear of leakage; (3) socio-cultural barriers, including cultural taboos, religious norms, and family-imposed restrictions; (4) institutional and environmental barriers, manifested as inadequate school sanitation facilities, lack of menstrual hygiene products, and unsupportive physical education policies; and (5) informational barriers, reflecting poor menstrual health literacy and inadequate teacher training. Notably, socio-cultural and environmental barriers were most pronounced in low- and middle-income countries (LMICs), while psychological barriers exhibited greater prevalence across high-income settings. Intersectionality of race, socioeconomic status, and geographic context significantly moderated the nature and intensity of these barriers. Conclusions: Barriers to PA during menstruation are multifactorial, deeply embedded in social and institutional structures, and disproportionately affect adolescent girls from marginalized communities. A comprehensive, context-sensitive, and intersectional approach — integrating school-based menstrual health education, infrastructural improvements, and policy reform — is urgently needed to address these barriers. This review calls for global concerted action to dismantle menstrual stigma and ensure equitable PA access for all adolescent girls.